Bioinformatics analysis of laryngeal squamous cell carcinoma based on the high infection rate of HPV in Northwest China - Fan Guo; Shurong Li; Shiqi Yan; Yuqiao Zhang; Guangke Wang; Ruixia Ma (PeerJ)
Background An increasing number of studies have demonstrated that human papillomavirus (HPV) plays a crucial role in the occurrence and development of laryngeal cancer. The present study aims to identify the differentially expressed genes and pathways in HPV-positive and HPV-negative laryngeal squamous cell carcinoma (LSCC) cells for the diagnosis and treatment of HPV-related LSCC, and to determine the prevalence rate of HPV in laryngeal cancer in Northwest China. Methods PCR-reverse dot blot was used to detect HPV genotypes in 115 LSCC patients’ paraffin sections from Jan 2022 to Jun 2024.HPV-positive TU212 cells (TU212HPV) were constructed via lentiviral transfection. RT-qPCR and Western blot detected mRNA and protein levels. RNA-seq and TMT sequenced gene and protein differences. DAVID database was used for Gene Ontology and pathway enrichment analyses. STRING and Cytoscape screened key genes and further analyzed pathways. Results Among 115 patients, 64 were HPV-positive (HPV16 being the most common, 57 cases). The TU212HPV cell line was successfully constructed. RNA-seq identified 1,336 differentially expressed genes (797 upregulated, 539 downregulated). TMT found 236 differentially expressed proteins (124 upregulated, 112 downregulated). The key genes were discovered to be EGFR, CDC42, PXN, SLC2A1, GAPDH, FGF2, ICAM1, ITGB1, SFN, PGK1, and ISG15. Pathway enrichment showed involvement in neuroactive ligand-receptor interaction, Cytoskeleton in muscle cell, transcriptional misregulation in cancer, etc. (P < 0.05). Conclusion HPV infection rate is 55.65% among laryngeal cancer patients in Northwest China. Ten key genes, namely EGFR, CDC42, PXN, SLC2A1, glyceraldehyde 3-phosphate dehydrogenase (GAPDH), FGF2, ICAM1, ITGB1, PGK1 and ISG15, as well as pathways like proteoglycans in cancer, regulation of actin cytoskeleton and HIF-1 signaling pathway are demonstrated to be of significance in the occurrence and development of laryngeal squamous cell carcinoma. PXN, ITGB1, ISG15, SLC2A1 and ICAM1 are regarded as potential therapeutic targets for HPV-positive laryngeal cancer. PXN and PGK1 are considered as potential prognostic markers for HPV-positive laryngeal cancer.